2010 Kansas Performance Tests With Soybean Varieties - Schapaugh, William T., Jr. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
Soybean performance tests are conducted each year to provide information on the relative performance of new and established varieties and brands at several locations in Kansas.
Keywords: Soybeans; Seeds; Yields; Environmental factors; Kansas